Host range and population density of the giant whitefly Aleurodicus dugesii Cockerell (Hemiptera: Aleyrodidae) on horticultural crops in Cipanas-Cianjur, West Java, Indonesia. Issue 1 (March 2020) - Hidayat, P; Maryana, E; Kusumah, Y M; Nurulaila, L
Abstract: The giant whitefly, Aleurodicus dugesii Cockerell (Hemiptera: Aleyrodidae) is a polyphagous insect which has a wide range of host plants. The insect is relatively a new pest to Indonesian agriculture. It was reported in 2008. The whitefly sucks on plant sap, extracting important nutrients that lead to defoliation, stunting and or plant death. Study of the host range and population density of the whitefly was conducted in horticultural crops at 5 villages in the Sub-district of Cipanas (Cianjur), West Java. Observation was done directly on the selected leaf samples. Twelve leaf samples were selected from four quadrants of the sample plants. The number of horticultural crops infested by the giant whitefly was 27 species consisted of 20 plant families. The most dominant host plants of the giant whitefly were families of Fabaceae, Solanaceae, and Euphorbiaceae, respectively. The highest population density of the giant whitefly was recorded on tamarillo ( Solanum betaceum ) as much as 1, 986 per leaf. The result of this research revealed that the giant whitefly was a potential important pest which had a wide range of host plants, resulted in severe damages to horticultural crops.